The Role of Antibiotic Prophylaxis in Anastomotic Leak Prevention during Elective Colorectal Surgery: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Lidia Castagneto-Gissey; Maria Francesca Russo; James Casella-Mariolo; Angelo Serao; Rosa Marcellinaro; Vito D'Andrea; Massimo Carlini; Giovanni Casella (MDPI AG, 2023)
Introduction: Despite several perioperative care advancements and innovations in surgical procedures and technologies, the incidence rate of anastomotic leaks (ALs) after colorectal surgery has not substantially decreased. Gut microbiota can play a critical role in the healing process of anastomotic tissue and alterations in its composition may be largely to blame for anastomotic insufficiency. The use of specific antibiotics for preoperative large bowel decontamination could significantly influence the rate of ALs. The aim of this study was to systematically assess the various antibiotic prophylactic regimen strategies for primary prevention of ALs during colorectal surgery, in view of the available evidence. Methods: A systematic review of the literature was conducted, and randomized clinical trials (RCTs) analyzing prophylactic antibiotic bowel preparation in colorectal surgery were included. PubMed, Embase, the Web of Science Core Collection, and the Cochrane Central Register of Controlled Trials were searched from inception through to 30 November 2022. The methodological quality of the included trials was evaluated. The primary outcome was AL rate; secondary outcomes were superficial/deep surgical site infections (SSIs). The PRISMA guidelines were used to carry out the present systematic review. Results: Thirteen RCTs published between 1977 and 2022, with a total of 4334 patients were included in the meta-analysis. Antibiotic prophylaxis was administered orally in 11/13 studies and intravenously in 2 studies. Patients randomly assigned to antibiotic prophylaxis, regardless of the regimen, had a reduced risk of ALs (p = 0.003) compared to mechanical bowel preparation (MBP) alone. The use of antibiotic prophylaxis was also more effective in significantly reducing SSIs (p < 0.001). Conclusions: The evidence points to an advantage of oral antibiotic prophylaxis in terms of AL rate, a significant contributor to perioperative morbidity, mortality, and rising healthcare expenditures. In light of such results, the use of antibiotic prophylaxis should be strongly encouraged prior to colorectal surgery.